Perception of refractive surgery among undergraduate medical students and their preferred method of refractive correction - Puri, Sanjeev Kumar; Elangovan, Suma (International Journal of Research in Medical Sciences, 2016)
Background: Refractive errors are a major cause of defective visual acuity in all age groups. Spectacles are the traditional and most widely used method of optical correction among all age groups. The main objective was to study the perception about refractive surgery among undergraduate medical students with refractive errors and their preferred method of refractive correction. Methods: A questionnaire based study was conducted among 227 undergraduate medical students with refractive errors. Results: Among 227 students, the prevalence of myopia was 89.42% and hypermetropia was 10.13%.There was one case of keratoconus (0.44%). None of them had undergone refractive surgery. 84.14 % were using only spectacles for correction of refractive error. 13.21% were using contact lenses. 0.88% was using both. Among spectacle users, 71.35% were satisfied with the use of spectacles, the reasons being ease of use and maintenance. 35.41% were not satisfied with spectacles and the main reason was dependency. Among the spectacle users, 23.56% wanted to switch over to contact lenses and the main reason was cosmetic. 92.51% were aware of refractive surgery, out of which 36.66% were willing to undergo refractive surgery. 65.92% were not willing to undergo refractive surgery, the main reason being risk of complications. Conclusions: The preference and willingness to undergo refractive surgery was less due to the fear of complications and the cost of the procedure. Spectacles remain the most preferred method the main reason being ease of use and it is maintenance free. Contact lenses are the next preferred method and the main reason was cosmetic.